Midwives’ Knowledge and Use of Decision-making Tools for Prevention of Obstetric-fistula among Pregnant Women in Abuja General Hospitals - (:unkn) unknown (My University, 2024)
Obstetric fistula, an improper connection between the genital tract and urinary or digestive tract, poses a significant public health concern, especially in sub-Saharan Africa and Southeast Asia.This study aimed to assess midwives' knowledge and use of clinical decision-making tools for preventing obstetric-fistula among pregnant women within general hospitals in FCT Abuja, Nigeria. Conducted through a descriptive cross-sectional research design, the study employed a stratified random sampling technique, dividing Abuja into six strata representing Area Councils. One general hospital was randomly selected from each stratum by simple random technique. All 132 midwives working in the Maternal Health Service Units of the selected hospitals participated. Data collection utilized a self-structured questionnaire with multiple-choice questions and a 4-point Likert scale, exhibiting high reliability (Cronbach's alpha = 0.732). Statistical analysis employed SPSS version 26, analyzing demographic information through frequency and percentages. Research questions were addressed using mean ratings and confidence intervals, while hypotheses were tested using Chi-Square and Pearson Product Moment Correlation at a significance level of 0.05. Midwives demonstrated a high level of proficiency in utilizing established guidelines and best practices for preventing obstetric-fistula across prenatal, intrapartum, and postpartum periods (grand mean: 3.55 at 95% confidence level), as well as in employing clinical decision-making tools for prevention of obstetric fistula (grand mean: 3.65 at 95% confidence level). In conclusion, midwives in Abuja exhibit high proficiency in the use of clinical decision-making tools for prevention of obstetric fistula. To further enhance their competency, continuous training and sustainability efforts are recommended.
Keywords: African Research